Radio signals from electron beams in terrestrial gamma ray flashes. Issue 5 (1st May 2013) - Connaughton, Valerie; Briggs, Michael S.; Xiong, Shaolin; Dwyer, Joseph R.; Hutchins, Michael L.; Grove, J. Eric; Chekhtman, Alexandre; Tierney, Dave; Fitzpatrick, Gerard; Foley, Suzanne; McBreen, Shelia; Bhat, P. N.; et al.
Abstract: [1] We show that the rate of association between terrestrial gamma ray flashes (TGFs) observed by the Fermi gamma ray burst monitor and VLF discharges detected by the World Wide Lightning Location Network (WWLLN) depends strongly on the duration of the TGF, with the shortest TGFs having associated WWLLN events over 50% of the time, and the longest TGFs showing a less than 10% match rate. This correlation is stronger if one excludes the WWLLN discharges that are not simultaneous (within 200 µs) with the TGF. We infer that the simultaneous VLF discharges are from the relativistic electron avalanches that are responsible for the flash of gamma rays and the nonsimultaneous VLF discharges are from related intracloud lightning strokes. The distributions of far‐field radiated VLF stroke energy measured by WWLLN for the simultaneous and nonsimultaneous discharges support the hypothesis of two discrete populations of VLF signals associated with TGFs, with the simultaneous discharges among the strongest measured by WWLLN. Key Points: Short TGFs have high match rate with WWLLN. TGF electrons emit radio signal TGFs are also associated with lightning events, less often seen by WWLLN The TGF radio signal is much more powerful than the lightning signal